Preliminary study on the treatment of prepubescent adolescent idiopathic scoliosis with Schroth exercises combined with core exercises - Jiang, Han-tao; Chen, Jia-yan; Wu, Feng-ze; Chen, Shu-jun; Wang, Wei-qiang; Wu, Min-jiao (Frontiers in Rehabilitation Sciences, 2025)
BackgroundAdolescent Idiopathic Scoliosis (AIS) is a common spinal deformity affecting 1%–3% of adolescents aged 10–18, characterized by a lateral curvature with a Cobb angle ≥10°. Current treatments, including bracing and surgery, have limitations in patient compliance and invasiveness, highlighting the need for effective non-surgical alternatives.MethodsThis retrospective cohort study included five prepubescent patients (age 10–14 years, Tanner Stage 1–2) with moderate AIS (Cobb angle 20°–40°). The intervention combined Schroth exercises with core exercises, performed 3–4 times daily over six months. Cobb angles were measured from standing full-spine radiographs at baseline and six months, while quality of life was assessed using the Scoliosis Research Society-22 (SRS-22) questionnaire.ResultsThe mean Cobb angle significantly reduced from 24.12° ± 4.80° at baseline to 12.68° ± 8.11° post-intervention (p = 0.012). Quality of life improved across all SRS-22 domains, with statistically significant gains in pain (p < 0.001), function (p = 0.011), mental health (p < 0.001), and self-image (p < 0.001). These findings suggest that the combined intervention effectively addresses spinal alignment and muscle strength, leading to improved clinical outcomes.ConclusionThis preliminary study demonstrates that combining Schroth exercises with core exercises is a promising non-surgical intervention for prepubescent AIS patients, significantly reducing Cobb angles and improving quality of life. Future research should include larger cohorts and longer follow-up periods to validate these findings and explore the long-term benefits of this combined approach.